1998
DOI: 10.1103/physrevlett.80.3964
|View full text |Cite
|
Sign up to set email alerts
|

Spectra of Decaying Turbulence in a Soap Film

Abstract: Grid turbulence in a flowing soap film is investigated with ambient pressure P as one of the control parameters. Reducing P significantly decreases air drag thus minimizing three-dimensional effects on the flowing film. It was found that while the total kinetic energy 1 2 ͗y 2 ͘ R E͑k͒ dk of velocity fluctuations increased noticeably as P was reduced, the energy spectrum E͑k͒ for wave numbers greater than the injection scale was remarkably insensitive to the pressure change, and obeyed a power law E͑k͒ ϳ k 23.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
62
1
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 14 publications
13
62
1
2
Order By: Relevance
“…R λ > 100) and constantly forced throughout the fluid volume so that and β remain constant (Kellay and Goldburg 2002). These scaling predictions have been confirmed for grid turbulence in a flowing soap film (Couder et al 1989;Martin et al 1998;Rutgers 1998;Kellay and Goldburg 2002). Based on the analytical result here between α and m, the inverse cascade is characterised by m → 3, and the predicted α → −1 consistent (in the limit) with the Batchelor spectrum (Batchelor 1959) for passive scalars in quasi two-dimensional turbulence.…”
Section: Two-dimensional Turbulence and The Inverse Cascadesupporting
confidence: 66%
“…R λ > 100) and constantly forced throughout the fluid volume so that and β remain constant (Kellay and Goldburg 2002). These scaling predictions have been confirmed for grid turbulence in a flowing soap film (Couder et al 1989;Martin et al 1998;Rutgers 1998;Kellay and Goldburg 2002). Based on the analytical result here between α and m, the inverse cascade is characterised by m → 3, and the predicted α → −1 consistent (in the limit) with the Batchelor spectrum (Batchelor 1959) for passive scalars in quasi two-dimensional turbulence.…”
Section: Two-dimensional Turbulence and The Inverse Cascadesupporting
confidence: 66%
“…In an earlier experiment, it was shown that weakening of the viscous coupling to air by enclosing the film in partial vacuum does not alter the velocity power spectrum of 2D grid turbulence even though the overall fluctuation is increased. 38 In the present case, however, it is unclear if the density power spectrum, which is to be reported below, is also unaffected by the thermal coupling term in Eq. ͑2͒ or ͑5͒.…”
Section: ͑3͒mentioning
confidence: 84%
“…In 2D turbulence of incompressible flows, the KolmogorovKraichnan scaling was found to describe rather well within the experimental precision the energy cascade [11,12]. In the enstrophy cascade, data from experiments [13] and numerical simulations [14,15] showed exponents that vary between ÿ3 and ÿ4. The surface friction forces present in the different experiments are believed to play a role in setting the scaling exponent [16].…”
mentioning
confidence: 94%